2008
DOI: 10.1097/brs.0b013e318160455c
|View full text |Cite
|
Sign up to set email alerts
|

Early Opioid Prescription and Subsequent Disability Among Workers With Back Injuries

Abstract: Prescription of opioids for more than 7 days for workers with acute back injuries is a risk factor for long-term disability. Further research is needed to elucidate this association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
139
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(151 citation statements)
references
References 18 publications
10
139
1
1
Order By: Relevance
“…Subsequent epidemiologic studies report similar findings [41,42]. A large body of literature now exists, demonstrating low levels of return to work for injured workers treated with opioids relative to those not receiving opioids [43][44][45][46][47]. Evidence is accumulating that patients treated with opioids who remain on the treatment for more than 90 days are likely to dose-escalate and are unlikely to discontinue the therapy [48,49].…”
Section: Effectivenessmentioning
confidence: 62%
“…Subsequent epidemiologic studies report similar findings [41,42]. A large body of literature now exists, demonstrating low levels of return to work for injured workers treated with opioids relative to those not receiving opioids [43][44][45][46][47]. Evidence is accumulating that patients treated with opioids who remain on the treatment for more than 90 days are likely to dose-escalate and are unlikely to discontinue the therapy [48,49].…”
Section: Effectivenessmentioning
confidence: 62%
“…60 Two recent publications have documented that the use of opioids within the WC setting, for both acute and chronic back pain, is significantly associated with increased risk for work disability at one-year. 44,[61][62][63] While surgical patients from this patient population have been identified as having increased rates of post-rehabilitation healthcare utilization, 64 the increased treatment seeking by patients may be in the service of maintaining their opioid dependence. 63 Further support for this hypothesis comes from the fact that data on more recent 2010-11 outcomes has seen the treatment seeking from new healthcare providers decrease 60-80% into the single digits (as measured on a quarterly basis), possibly due to more effective pain medication management and patient-negotiated opioid tapering.…”
Section: Discussionmentioning
confidence: 99%
“…[59][60][61][62] However, few studies focus on (or even include) WC claim patients. With the exception of two studies, 41,59 no other previous studies have looked at a population of extreme lengths of disability after WC claims receiving one or more fusions or other spinal procedure in a continuum of care (i.e., surgery followed by active rehabilitation).…”
Section: Discussionmentioning
confidence: 99%
“…Franklin and his colleagues examined whether prescription of opioids within 6 weeks of low back injury was associated with work disability at 1 year [49]. They found that more than one third of the workers received an opioid prescription within the first six weeks, with about 50% received at the first medical visit.…”
Section: Opioids and Disabilitymentioning
confidence: 99%